Use of antihypertensive drugs and risk of skin cancer. (15th January 2015) - Schmidt, S.A.J.; Schmidt, M.; Mehnert, F.; Lemeshow, S.; Sørensen, H.T.
Abstract Background Several antihypertensive drugs are photosensitizing and may therefore act as cocarcinogens with ultraviolet radiation. Objective To examine whether antihypertensive drug use is associated with squamous cell carcinoma (SCC), basal cell carcinoma (BCC), and malignant melanoma (MM). Methods We used population‐based databases to conduct a case–control study including all first‐time cases of SCC (n = 2282), BCC (n = 17 242), and MM (n = 3660) in northern Denmark, 1991–2010. We matched approximately 10 controls (n = 231 743) to each case by age, sex and county using risk‐set sampling. We used conditional logistic regression to compute odds ratios (ORs) for skin cancer with 95% confidence intervals comparing ever users of antihypertensives (>2 previous prescriptions) with non‐users (≤2 previous prescriptions). We adjusted for comorbidity and comedications. We further analysed use by duration (short term: <5 years; long term: ≥5 years) and intensity (low intensity or high intensity: <50% or ≥50% prescription coverage during total duration of use, respectively). Results Ever users of diuretics were at increased risk of SCC (OR 1.19; 1.06–1.33), driven by potassium‐sparing agents alone (OR 1.40; 1.09–1.80) or with low‐ceiling diuretics (OR 2.68; 2.24–3.21) and by long‐term use (OR 1.41; 1.16–1.72 at low intensity; OR 1.44; 0.98–2.14 at high intensity). Ever users of sulphonamides (OR 1.49; 1.04–2.12) and non‐aldosterone antagonist potassium‐sparing agents (OR 2.26; 0.85–6.01) were at increased MM risk. The latter was also associated with BCC (OR 1.47; 1.00–2.17), as was low‐ceiling diuretics combined with potassium‐sparing agents (OR 1.23; 1.12–1.35). Long‐term, low‐intensity (OR 1.53; 1.05–2.23) and high‐intensity (OR 1.44; 0.56–3.69) angiotensin receptor blocker use was associated with MM. Estimates for angiotensin‐converting enzyme inhibitors, β‐blockers, and calcium channel blockers were inconsistent or weak (<20% increased). Conclusion Long‐term angiotensin receptor blocker use was associated with risk of MM. Moreover, long‐term diuretic use was associated with SCC risk, driven by potassium‐sparing agents alone or in combination with low‐ceiling diuretics.